Employee Self-Determination in Power and Management Relations Structure - S V Gulenina (Peoples' Friendship University of Russia (RUDN University), 2011)
The article is devoted to the problem of self-determination of the employee in the field of the power relations represented by the subject and the object aspects; to the psychological basis of the identity of these aspects as a mechanism for optimizing psychological modality of the proper, desirable and possible.